(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
Formation of creativity in elementary school students is important for increasing their success in the educational process and developing innovative thinking skills in the future. By introducing modern technologies into the educational process, the effectiveness of teaching creative skills increases significantly. This topic aims to enrich the educational process with the help of technological tools (for example, interactive programs, virtual laboratories and creative applications) that arouse children’s interest and stimulate creative thinking. This approach not only facilitates the learning process of students, but also develops their self-confidence and innovative approach skills.